Existence value, biodiversity, and the utilitarian dilemma - Bartosz Bartkowski (Helmholtz-Zentrum für Umweltforschung (UFZ), 2017)
Existence value has been argued to be a significant part of the total economic value of some ecosystems. However, its compatibility with the welfare economic foundations of economic valuation is very limited - it is difficult to logically conceive of changes in existence. Moreover, when applied to biodiversity, the concept of existence value gives rise to an instance of a more fundamental problem of economic valuation, termed here the utilitarian dilemma: it can be argued conceptually that biodiversity cannot have existence value; yet the results of empirical studies suggest that people in stated preference studies can be expected to assign existence value to it. The utilitarian dilemma arises as the analysing economist must deal somehow with 'erroneous' preferences. There seems to be no simple solution to the dilemma, but deliberative monetary valuation has the potential to alleviate it.
Keywords: 330; axiology; biodiversity; economic valuation; existence value; utilitarianism